2019
DOI: 10.32394/rpzh.2019.0071
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mass Index and dietary behaviours of the Polish Border Guard officers

Abstract: Background. Due to specific requirements of service, Border Guard officers should be characterized by good health. Whereas there is lack of studies assessing nutritional status as well as dietary behaviours among Polish Border Guard officers. Objective. The aim of the study was to assess the impact of dietary behaviours of the Polish Border Guard officers on the Fat Mass Index. Material and methods. The study was carried out with participation of 250 Border Guard officers (187 men and 63 women), aged 37±6; yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Nutritional imbalance leads to the appearance of excess adipose tissue. Such a conclusion is stated in work [7] after researching the nutritional status of the officers of the border service of Poland. The authors identified the main cause of the violation.…”
Section: Literature Review and Problem Statementmentioning
confidence: 93%
“…Nutritional imbalance leads to the appearance of excess adipose tissue. Such a conclusion is stated in work [7] after researching the nutritional status of the officers of the border service of Poland. The authors identified the main cause of the violation.…”
Section: Literature Review and Problem Statementmentioning
confidence: 93%
“…The body mass composition of patients was evaluated with the 780 MA Tanita MC analyzer, which is based on the measurement of electrical bioimpedance [ 32 , 33 ]. The analyzer is able to carry out a segmental body assessment, including of adipose tissue (fat) and muscle mass, which is divided into right and left arm, right and left leg, and trunk.…”
Section: Methodsmentioning
confidence: 99%
“…The ADI for nitrite is 0.07 mg nitrite ion/kg bw/day [12] and for nitrate it is 3.7 mg nitrate ion/kg bw/day [13]. The toxicity of a food additive and its dietary intake determine the extent to which it may represent a health concern [9] and negative health impacts may arise when ADIs are surpassed [14]. Thus, intakes must be monitored by member states in order to facilitate risk assessment [5], through a scientifically based four-step procedure comprising of hazard identification, hazard characterization, exposure assessment and risk characterization, which is used to estimate the proportion of individuals and age-groups that exceed these limits, for public health monitoring [15].…”
Section: Introductionmentioning
confidence: 99%